The cursed carolers in context
1 online resource (xi, 173 pages)
Keywords: "The Cursed Carolers in Context explores the interplay between the forms and contexts in which the tale of the cursed carolers circulated, and the meanings it had for medieval and early modern authors and audiences. The story of the cursed carolers has circulated in Europe since the eleventh century. In this story, a group of people in a village in Saxony skip Christmas mass to perform a circle dance in the cemetery, only to be cursed and forced to keep dancing for a whole year. By approaching the story in specific historical contexts, this book shows how the story of the cursed carolers became a space in which medieval readers, writers, and listeners could debate the meaning and significance of a surprising variety of questions, including ecclesiastical authority, gender roles, pastoral responsibility, and even the conduct of crusades. This consideration of the interplay between text and context sheds new light on how and why the story of the dancers achieved such popularity in the Middle Ages, and how its meanings developed and changed throughout the period. This book will appeal to scholars and students of medieval European history, literature, and dance, as well as those interested in cultural history"--